Unlocking Firm Level Productivity and Promoting More Inclusive Growth : The Role of Innovation in Ethiopia - World Bank Group (World Bank, Washington, DC, 2016)
Rapid and consistent economic growth of Ethiopia over the past decade has contributed to reducing the number of people living in poverty. The Government of Ethiopia has created the growth and transformation plan (GTP), focusing on two overarching themes: fostering competitiveness and employment, and enhancing resilience and reducing vulnerabilities. This plan recognizes that for poverty reduction and economic growth to be sustainable, the Ethiopian economic structure will have to undergo a fundamental transformation. In accordance with a focus on poverty reduction and economic growth, the GTP has identified five main levers for change: public sector investment in infrastructure to lay the ground for private sector development, enhancement of policies and regulations to provide an environment conducive to competitiveness and productivity, expanding access to credit for small and medium size enterprises, provision of training and education to augment the supply of skilled labor, and improved access to land. Technological adoption and innovation will play a crucial role in delivering the goals laid out in the GTP. Participation in foreign markets also induces firms to become more innovative, a phenomenon known as learning through exporting, as observed among Ethiopian leather exporters. Another vital determinant of innovative activity is the accumulation of human capital and the skill level of the workforce. This study seeks: (i) to empirically analyze the extent of innovative activities that formal firms are undertaking in Ethiopia; (ii) to conduct a review of the existing innovation landscape; and (iii) to identify opportunities to foster innovations at the base of the pyramid (BoP) in Ethiopia. This study is structured as follows: chapter one gives introduction. Chapter two provides a detailed overview of the characteristics of growth and innovation, by providing key insights based on the enterprise survey analysis on the characteristics, motivations, operational and market environment and constraints of the innovators in Ethiopia. Chapter three assesses the innovation landscape in Ethiopia, by looking at the governmental and private agencies responsible to promote innovation, as well as active programs, and donor initiatives which may play a role in promoting firm level and pro-poor innovations. Chapter four provides policy recommendations to promote innovation in Ethiopia both at the firm level and in the form of pro-poor initiatives.